Pengeringan Produk Tanaman Herbal di Kelurahan Bubulak - Inti Putri Madinah; I Wayan Astika (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Traditional medicine is the cultural heritage of the Indonesian people that needs to be preserved and developed to support health, one of which is herbal medicine using herbal plants. Community service activities at Bubulak Urban Village, West Bogor sub-district, Bogor City were found to be ready for consumption. One of them is the drying process so that the plants can last a long time and reach consumers. In RW 06, Bubulak, there is Mr. Ma'mun who processes herbs. The method used is interviews and observations so that concluded the processing of herbal plants is an indirect drying technique and can last up to three months. One of the supporting factors is packaging with plastic and storing it in a dry place. Keywords : community, drying, herbal plants, service